Cover Feature: Lipase and Laccase Encapsulated on Zeolite Imidazolate Framework: Enzyme Activity and Stability from Voltammetric Measurements (ChemCatChem 23/2018). Issue 23 (7th December 2018) - Naseri, Maryam; Pitzalis, Federica; Carucci, Cristina; Medda, Luca; Fotouhi, Lida; Magner, Edmond; Salis, Andrea
Abstract : The Cover Feature shows lipase and laccase that were encapsulated in ZIF‐8 and ZIF‐zni metal organic framework materials using a one‐pot synthesis‐immobilization method in aqueous solution at room temperature. In their Full Paper, M. Naseri et al. demonstrate that ZIF‐zni‐immobilized laccase retains a high level of activity, whereas Lac@ZIF‐8 is the most stable system on storage (15 days at 5 °C), retaining 94 % of initial activity. Lip@ZIF‐zni biocatalyst has an optimal level of reusability. More information can be found in the Full Paper by M. Naseri et al. onpage 5425 in Issue 23, 2018 (DOI:10.1002/cctc.201801293 ).